1992
DOI: 10.3109/02656739209037994
|View full text |Cite
|
Sign up to set email alerts
|

Winner of the Lund Science Award 1992 Thermosensitization induced by step-down heating: A review on heat-induced sensitization to hyperthermia alone or hyperthermia combined with radiation

Abstract: A few minute's exposure to a high temperature (sensitizing treatment, ST) may substantially increase the cytotoxic and the radiosensitizing effect of a subsequent heating at a lower temperature (test treatment, TT). This phenomenon, which is known as step-down heating (SDH) or thermosensitization, has been observed both in cultured cells in vitro and in tumours and normal tissues in vivo. The effect of SDH increases with a lowering of TT temperature, but it is rapidly lost at temperatures very close to 37 degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 86 publications
2
7
0
Order By: Relevance
“…The magnitude of the SDH effect in the xenograft lines was similar to that reported for the rodent tumour lines. The present study thus adds further support to the suggestion that the SDH effect is a general biological phenomenon applying also to clinical hyperthermia of human tumours (Lindegaard, 1992 Heat-induced vessel occlusion in tumours leads to secondary cell death (Kang et al, 1980;Rofstad & Brustad, 1986a), i.e. the tumour cells that were fully supplied by the collapsed vessels die because of rapid exhaustion of the oxygen and nutrient pools and/or accumulation of acidic waste products.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The magnitude of the SDH effect in the xenograft lines was similar to that reported for the rodent tumour lines. The present study thus adds further support to the suggestion that the SDH effect is a general biological phenomenon applying also to clinical hyperthermia of human tumours (Lindegaard, 1992 Heat-induced vessel occlusion in tumours leads to secondary cell death (Kang et al, 1980;Rofstad & Brustad, 1986a), i.e. the tumour cells that were fully supplied by the collapsed vessels die because of rapid exhaustion of the oxygen and nutrient pools and/or accumulation of acidic waste products.…”
Section: Discussionsupporting
confidence: 64%
“…However, it has been suggested that the SDH effect might be explained in terms of inhibition of repair of sublethal heat damage (Henle, 1980) or enhanced conversion of sublethal heat damage into lethal damage (Jung, 1986;Henle, 1987;Lindegaard & Bentzen, 1993). SDH could be of direct clinical importance, sine even a short exposure to high temperature might increase the effect of an otherwise inadequate heat treatment (Lindegaard, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The present experiments are in agreement with these observations. SDH did not hamper the development of neither CIT nor AIT, thereby giving further support to the idea that thermosensitization and thermotolerance are independent phenomena (Jung 1982, Henle 1987, Lindegaard 1992.…”
Section: Discussionsupporting
confidence: 61%
“…Thermosensitization is observed with a high-tolow temperature sequence (step-down heating, SDH) and leads to an increased sensitivity to heating at the lower temperature (Joshi and Jung 1979, Henle 1980, Jung and Kolling 1980, Jung 1982, Lindegaard 1992. Thermotolerance can be expressed in at least two ways (Henle and Dethlefsen 1978, Bauer and Henle 1979, Field and Anderson 1982, Jung 1982, Dikomey et al 1984, Nielsen 1984, Henle 1987.…”
Section: Introductionmentioning
confidence: 99%